2013
DOI: 10.1016/j.aat.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the cannabinoid system for pain relief?

Abstract: Marijuana has been used to relieve pain for centuries, but its analgesic mechanism has only been understood during the past two decades. It is mainly mediated by its constituents, cannabinoids, through activating central cannabinoid 1 (CB1) receptors, as well as peripheral CB1 and CB2 receptors. CB2-selective agonists have the benefit of lacking CB1 receptor-mediated CNS side effects. Anandamide and 2-arachidonoylglycerol (2-AG) are two intensively studied endogenous lipid ligands of cannabinoid receptors, ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 163 publications
0
26
0
Order By: Relevance
“…Studies have shown that cannabinoids acting through central CB1 receptors, and possibly peripheral CB1 and CB2 receptors, 63 play important roles in modeling nociceptive responses in various models of pain. These findings are consistent with reports that marijuana may be effective in ameliorating neuropathic pain, 64,65 even at very low levels of THC (1.29%).…”
Section: Figurementioning
confidence: 99%
“…Studies have shown that cannabinoids acting through central CB1 receptors, and possibly peripheral CB1 and CB2 receptors, 63 play important roles in modeling nociceptive responses in various models of pain. These findings are consistent with reports that marijuana may be effective in ameliorating neuropathic pain, 64,65 even at very low levels of THC (1.29%).…”
Section: Figurementioning
confidence: 99%
“…CB analgesia in both chronic and acute pain models is mediated through CB1 and CB2 receptors that are differentially expressed in the central and peripheral nervous systems [9,10]. An emerging body of literature supports the notion that endocannabinoid systems may also modulate CIN.…”
Section: Introductionmentioning
confidence: 89%
“…Selective FAAH inhibitors enhance anandamide endogenous levels that cause antinociceptive effect by agonism on the CB 2 receptor [21]. Furthermore, many preclinical studies demonstrated that FAAH inhibitors reduce chronic pain without the development of tolerance after repeated administrations [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maca improves the antioxidant cell machinery [19]. Cannabinoid and cholinergic systems [20,21], as well as redox unbalance [22][23][24][25], play a relevant role in persistent pain processes. Maca consumption has been associated with lower serum levels of the proinflammatory and proalgic cytokine IL-6 in populations living in the Peruvian Central Andes [8].…”
Section: Introductionmentioning
confidence: 99%